Venezuela: Universities at Risk in a Failed State - Navarro, Juan (International Higher Education, 2023)
Deep economic decline and a prolonged political crisis in Venezuela have had a negative impact on higher education institutions. The main public universities, in particular, have paid a heavy price as a consequence of their defense of democratic values and academic freedom, as they have been defunded by the government. Amid severe brain drain and political and economic distress, some positive signs provide reasons for hope, but no recovery can be anticipated.